2019
DOI: 10.1097/md.0000000000015143
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction as the first manifestation of Takayasu arteritis

Abstract: Rationale: Takayasu arteritis (TA) is a chronic inflammatory disease involving the aorta and its major branches. Initial diagnosis is usually difficult due to the highly variable symptoms. Acute myocardial infarction (AMI) is a very rare presentation in patients with TA. Moreover, the choice of early management for these patients is not well established. Patient concerns: A 34-year-old woman was taken to the Emergency Department of our hospital, presenting with a sudden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Takayasu’s arteritis may result in non-specific symptoms of upper body pain, intermittent claudication, headache, dizziness, syncope, and visual deterioration [ 6 ]. Involvement of aortic branches can result in malaise, headache, decreased to absent pulses of upper extremities, dysfunction of upper extremities, dizziness, visual disturbances, and syncope [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takayasu’s arteritis may result in non-specific symptoms of upper body pain, intermittent claudication, headache, dizziness, syncope, and visual deterioration [ 6 ]. Involvement of aortic branches can result in malaise, headache, decreased to absent pulses of upper extremities, dysfunction of upper extremities, dizziness, visual disturbances, and syncope [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the initial symptoms are non-specific, diagnosis is frequently delayed, often resulting in complications later in the course of diagnosis. One study reported a patient presenting with acute myocardial ischemia [ 6 ]. Our patient was diagnosed as a case of Takayasu’s arteritis based upon criterion proposed by the American college of rheumatology, of which our patient had four i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists the seven case reports of DES PCI in coronary TA. Cases 1, 3, 5, and 7 have reported PCI with DES with variable durations of follow‐up ranging from 12 weeks to 4 years 6,11‐13 . Yokota et al (case 5) described a case of a 52‐year‐old woman who was followed up over 4 years and required a total of four PCIs due to recurrent in‐stent restenoses 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for the young female patients with AMI, systemic disease such as TA should be taken into consideration. Several cases, primarily consisting of young women, have been reported to present AMI as the primary manifestation of TA ( 30 35 ). In a 5-year follow-up study, 9% (7/76) TA patients were detected to have AMI through echocardiography ( 4 ).…”
Section: Cardiovascular Complications Of Ta Patientsmentioning
confidence: 99%
“…Prompt and early treatment is essential to the TA patients with AMI. Thus, the medical team should take percutaneous coronary interventions as prioritizing and timely immunosuppressive therapy could improve the cardiac status and long-term outcome ( 30 , 36 ).…”
Section: Cardiovascular Complications Of Ta Patientsmentioning
confidence: 99%